Perbandingan Tingkat Kepercayaan Diri Antara Laki-Laki dan Perempuan yang Menjadi Pemimpin Organisasi Pada Mahasiswa - Innez Innez; Bernardinus Agus Arswimba (Universitas Sanata Dharma, 2025)
This study aims to determine the comparison of self-confidence levels between men and women in leading organizations in USD students. Then, to determine the level of self-confidence of men in leading organizations in USD students, and to determine the level of self-confidence of women in leading organizations in USD students. This study uses a comparative descriptive quantitative approach. The subjects of the study were students of Sanata Dharma University who were leaders of student organizations totaling 60 people, namely 30 women and 30 men. The data collection technique was through a questionnaire regarding the level of self-confidence. Valid research items in this study amounted to 59 valid items from a total of 60 items. The average score of male self-confidence was 181.733. While the average score of women was 204.933. The average score of women's self-confidence was higher than men. The level of self-confidence of men and women in becoming leaders of student organizations Most of them are in the very high category. The percentage of male self-confidence levels in the very high category is 63.3%, the high category is 16.7%, the medium category is 13.3%, the low category is 0% and the very low category is 6.7%. While the percentage of female self-confidence levels in the very high category is 86.7%, the high category is 10%, the medium category is 3.3%, the low category is 0% and the very low category is 0%.